The normative imperative: Sociopolitical challenges of strategic and organizational communication - Oliveira, Evandro (2023)
In this proceedings book, we can find 29 extended abstracts selected for presentation and discussion at the interim ECREA Organizational and Strategic Communication thematic session conference that took place from 5th to 7th of July 2023 at the Autonomous University of Lisbon, in a joint organisation with LabCom – Research centre, from the University of Beira Interior. Some of the topics debated along the conference were: normative governance for organizational communication and strategic communication; impact of rhetoric, persuasion and brand narratives on society; public sector implications of normative dimensions; nonprofit and hypocrisy; impact of communication on consumers identity and well-being; B-corps as a new relationship management approach; accountability, integrated reporting and communication; greenwashing and other “image” washing; internal relationship management and well-being; corporate social advocacy and CEO activism.